Modelling of Damage Spatiotemporal Distribution in Saturated Cementitious Materials and its Chloride Transport Evolution - Liu, Zhiyong; Qian, Rusheng; Gao, Sen; Wang, Yuncheng; Jiang, Jinyang; Zhang, Yunsheng (Journal of advanced concrete technology, 2023)
Crack-induced damage significantly affects the chloride transport mechanism in cementitious materials. To quantitatively evaluate the crack effects, a coupled model was proposed in this paper for saturated cement paste with various uniaxial tensile damage. First, the 3D microstructure of hydrating cement paste was simulated based on a voxel-based hydration model, and its damaged spatiotemporal distribution under uniaxial tensile stress was simulated using a finite-element model. Based on the damaged cement paste, an electrical Modelling framework was presented to simulate the chloride transport. The results show that the damage spatiotemporal distribution in saturated cementitious materials with uniaxial tensile and its chloride transport evolution can be successfully modelled using the self-created model and coupled method. the damage of cementitious material is an accumulation process of cracks spread over the main crack. During the process, the crack connectivity and crack width affect chloride transport and its fracture-volume threshold value is 1.40%. Compared to studies published, the coupled model could well simulate chloride transport in saturated cementitious materials with uniaxial tensile damage.